Isotopic composition and hydrogeochemistry of a periglacial Andean catchment and its relevance in the knowledge of water resources in mountainous areas - Sileo, Noelia Romina; Dapeña, Cristina; Trombotto, Dario Tomas (Isotopes in Environmental and Health Studies)
Glacial and periglacial basins contain the largest reserves of fresh water in the world. These areas are extremely sensitive to global warming and climate change. The dry Andes of South America are characterized by large periglacial areas. This study focuses on the water isotopic composition and hydrochemistry of a typical periglacial environment of the Andes, in the Vallecitos catchment (2400–5500 m a.s.l.), Cordillera Frontal, Argentina. Detailed fieldwork was conducted between 2013 and 2017 with 240 samples collected for major ions and physicochemical parameters, and 67 samples analysed for 2H and 18O. The chemical composition of precipitation is typical Ca-HCO3, while streams and groundwaters are Ca-MgSO4 type. The isotope content of precipitation shows a wide dispersion. The snow samples are in general more depleted than the rainfall. Some springs vary their composition seasonally, associated to the melting of perennial snow patches. In general, all samples from the upper basin present depleted isotope contents related to recharge at higher altitudes, whereas samples from the lower basin show more enriched values. Intermediate compositions reflect the melting of snow and degrading ice-rich permafrost. These results will give a better understanding of the dynamics of water to manage water resources. Fil: Sileo, Noelia Romina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Dapeña, Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Geocronología y Geología Isotópica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Geocronología y Geología ...